2018
DOI: 10.1186/s40101-018-0174-x
|View full text |Cite
|
Sign up to set email alerts
|

l-Menthol attenuates the magnitude of cold-induced vasodilation on the extremities of young females

Abstract: BackgroundMenthol chemically triggers cold-sensitive receptors in the skin without conductive skin cooling. We investigated the effects of menthol-induced activation of cutaneous cold receptors on the cold-induced vasodilation (CIVD) of the finger. We hypothesized that the menthol application would attenuate typical CIVD responses.Methods1.5% l-menthol was fully applied over the left hand and forearm, and then, the middle finger of the left hand was immersed into 4 °C water for 30 min. A trial consisted of 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Furthermore, whole-body application results in a slower decrease of rectal temperature comparing with cool water immersion, which was again attributed to peripheral vasoconstriction (Kounalakis et al, 2010) even though perfusion was not assessed. Similar results were found with the application of menthol on the trunk of mice (Tajino et al, 2019) and with the immersion of the upper extremities in cold water, in which menthol attenuated cold-induced restorative vasodilation (perfusion not assessed) (Kim and Lee, 2018). Taken together, these results suggest that application of menthol over a moderate/large skin surface initiates heat-conservation responses caused by cold perception.…”
Section: Menthol-induced Vasoconstrictionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, whole-body application results in a slower decrease of rectal temperature comparing with cool water immersion, which was again attributed to peripheral vasoconstriction (Kounalakis et al, 2010) even though perfusion was not assessed. Similar results were found with the application of menthol on the trunk of mice (Tajino et al, 2019) and with the immersion of the upper extremities in cold water, in which menthol attenuated cold-induced restorative vasodilation (perfusion not assessed) (Kim and Lee, 2018). Taken together, these results suggest that application of menthol over a moderate/large skin surface initiates heat-conservation responses caused by cold perception.…”
Section: Menthol-induced Vasoconstrictionsupporting
confidence: 77%
“…In the majority of studies assessing provoked skin, menthol has been found to increase microcirculatory perfusion, either by topical application (Crandall et al, 2002;Wasner et al, 2004;Kobayashi et al, 2005;Topp et al, 2013;Craighead and Alexander, 2016;Kim and Lee, 2018) or intradermal microdialysis (Hong and Shellock, 1991;Guimarães and Moura, 2001). When topically applied, menthol passively diffuses through the epidermis and reaches the dermal microvascular networks.…”
Section: Menthol-induced Vasodilationmentioning
confidence: 99%
“…L-Menthol is widely used in the food industry, daily-use chemicals, and medicine fields. 18,19 It can inhibit oxidative stress and inflammation, reduce thermal sensation, and may even be used in cancer therapeutics by inducing apoptosis. 20−23 The crystal products of L-menthol on the market are either needle-shaped or rod-shaped.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the similarity in the menthol biosynthetic pathway of these two species, the compositional variations in the essential oil cannot be ignored, as M. arvensis essential oil constitutes the major trading essential oil for menthol in the world. Likewise, menthol is a chemical cooling agent naturally produced from mint oils or prepared synthetically [157]. Consequently, a cold sensation in mammals is detected by several cold-sensors; among them, the most preeminent one is the cold and menthol receptor, canonical transient receptor potential cation channel subfamily M member 8 (TRPM8) [158].…”
Section: Food Compounds Related To the Browning Processmentioning
confidence: 99%